Informe técnico Consultorio Urbano y Patrimonial, Universidad de la Costa (2021)
The objective of this document is to make a detailed technical report of the entire process developed in the creation of the Urban Heritage Clinic, Universidad de la Costa (CUPUC). The project is carried out through the Territorial Management I Subject within the Framework of the Challenges Program, which solves the Challenge of the protection and conservation of the El Prado neighborhood of the City of Barranquilla. The study began with the identification of problems within the sector such as urban infractions within it, lack of guidance and knowledge on the part of the community itself regarding the conservation and care of the properties of the El Prado neighborhood. Taking all this into account, a portfolio of services was created that solves the Challenge of the protection and conservation of the Neighborhood, in which pedagogies, training, consultancies and identification of urban infractions and surveillance are provided.